Production of lignocellulose-degrading enzymes and changes in soil bacterial communities during the growth of Pleurotus ostreatus in soil with different carbon content - Snajdr, J; Baldrian, P (Folia microbiologica, 2006)
The extracellular enzyme activity and changes in soil bacterial community during the growth of the ligninolytic fungus Pleurotus ostreatus were determined in nonsterile soil with low and high available carbon content. In soil with P. ostreatus, the activity of ligninolytic enzymes laccase and Mn-peroxidase was several orders of magnitude higher than in soil without the fungus. Addition of lignocellulose to soil increased the activity of cellulolytic fungi and the production of Mn-peroxidase by P. ostreatus. The counts of heterotrophic bacteria were more significantly affected by the presence of lignocellulose than by P. ostreatus. The effects of both substrate addition and time (succession) were more significant factors affecting the soil bacterial community than the presence of P. ostreatus. Bacterial community structure was affected by fungal colonization in low carbon soil, where a decrease of diversity and changes in substrate utilization profiles were detected.
Keywords: Soil Microbiology; lignin; Laccase; Lignin; lakasa; peroxidasy; fungální proteiny; půda; půdní mikrobiologie; celulosa; uhlík; Cellulose; Fungal Proteins; Bacteria; Soil; Carbon; Pleurotus; Peroxidases